Synthesis and Crystal Structure of 3-(3,4-Dimethylbenzylidene)-1,5-dioxaspiro[5.5]undecane-2,4-dione - Zeng, Wulan (Asian Journal of Chemistry, 2011)
A new spiro compound 3-(3,4-dimethylbenzylidene)-1,5-dioxaspiro[5.5]undecane-2,4-dione was prepared by 1,5-dioxaspiro[5.5]undecane-2,4-dione with 3,4-dimethylbenzaldehyde in ethanol and its crystal structure was determined by X-ray crystallographic techniques. It crystallizes in monoclinic, space group Cc with a = 27.437(6) Å, b = 11.471(2) Å, c = 21.196(4) Å, b = 109.85(3)°, C18H20O4, Mr = 300.34, V = 6275(2) Å3, Z = 16, Dc = 1.271 g/cm3, F(000) = 2556, μ = 0.089 mm-1. The 1,3-dioxane ring is in a distorted envelope conformation while cyclohexane ring assumes a highly symmetric chair conformation.